Efficacy of artesunate-mefloquine combination therapy on survival in Plasmodium berghei-infected mice: a time-to-event analysis - Vieira Santos, Valdeene; Campos Pereira, Laiz; dos Santos Miranda, Aline Lorena Lourenço; Quadros, Helenita Costa; Magalhães Moreira, Diogo Rodrigo; Johansson Azeredo, Francine (Frontiers in Tropical Diseases, 2024)
Artesunate-mefloquine combination therapy (AR-MQ) is a standard therapy for treating uncomplicated malaria by Plasmodium falciparum. Time-to-event (TTE) analysis is used to describe the occurrence and timing of events by yielding information about the risk of an event occurring during a specific period. Therefore, the aim of the present study is to evaluate the efficacy of AR-MQ combination therapy on the survival time of Plasmodium berghei-infected mice using TTE analysis. Here, TTE analysis was used to analyze P. berghei-infected mice receiving a single oral dose of 100 mg/kg artesunate and 55 mg/kg mefloquine or dose-matched artesunate monotherapy. Median survival was higher for AR-MQ than for monotherapy. A survival analysis to evaluate the influence of treatment on survival was performed using MonolixSuite™. The Weibull model best described the mortality time of the animals. Subsequent analysis identified that AR-MQ had a significant influence on population survival time (Te_pop), estimated at 13.66 days, population parameter for curve fitting (p_pop) at 4.39, and survival time under AR-MQ treatment (beta Te_AR-MQ) at 0.77 days. The probability of survival 7, 15, and 30 days after treatment with AR-MQ was 94.4%, 88.9%, and 14.9%, respectively. The experimental and modeling data both found that AR-MQ combination therapy yielded increased survival of infected animals.